Attempts and outcomes of liquisolid technology: An updated chronological compilation of innovative ideas and adjuvants in the field - Vijay Sharma; Kamla Pathak (Mazandaran University of Medical Sciences, 2016)
It has been observed that most of the chemical entities have high lipophilicity and poor aqueous solubility, which result in poor bioavailability. In order to improve the bioavailability, the release behavior of such drugs should be improved. Although there are numerous techniques to handle solubility related issue, but they are expensive due to involvement of complicated equipments, advanced manufacturing operations that includes multiple and tedious steps. The liquisolid technology or powder solution technology is a promising technique for modifying the release characteristics of active pharmaceutical ingredients. As the liquisolid technology uses similar production processes as followed to develop a conventional tablet, but this technology to improve the release rate of poorly water soluble drugs is simple and cost effective The core concept of the technique involves, liquids such as solution/dispersion of poorly soluble drugs in a non-volatile solvent that is transformed into free flowing and desirable compression characteristics. To develop a fast-release liquisolid formulation, high amount of liquid vehicle is required while more effective tableting excipients with high liquid adsorption are needed to reduce the weight of the tablet. Simultaneously, this technology also has the capability to sustain the drug release and allow the development of sustained release formulation with desirable release kinetics. The present work deals with the chronological compilation and briefing of all the reported researches which involved the concept of underlined technology by the use of common as well as novel excipients to modify the release behavior of therapeutically active compounds.